The Analysis of the Ghana Telecom Industry - Alexander Osei-Owusu (International Telecommunications Society (ITS), 2015)
Drawing on institutional theory, this paper is aimed at providing further understanding and explanation to the Ghanaian telecom industry today. In particular the research sought to determine: how the industry was governed from the pre-reformation to the reformation period; the process of transitional reform and how it has molded the industry, especially on market competition; major policy initiatives and periods undertaken, since the beginning of the transitional process; how institutions have affected the reform of telecommunication in Ghana and to what extent various actors has impacted the industry. The study identified two major periods and their various level of governance, from the Nationalization period or era where management of the sector started from traditional leaders, later to municipalities/ districts and finally to the works and housing department; at the denationalization period or era management was solely in the hands of an independent and a national regulatory authority. It was also revealed three main policy direction across the period of reform: market liberalization (1997-2007) where Westel limited was introduced into the fixed line market, spacefon, celltell and mobitel all introduced into the cellular telephony market. At the beginning of 2008 policy was directed towards infrastructure expansion, as a result infrastructure licensing was introduced opening the door for international tower companies. Recently, from the beginning of 2011 up to date, policy is directed to consumer protection and projects such as Mobile Number Portability and SIM Card Identification has been rolled out. The use of the institutional theory provided further understanding of the sector reforms. In summation, the research also provided a full picture of how the Ghanaian telecom industry looks today.
Keywords: 330; Institutional theory; reforms; transitional reform; Nationalization; denationalization